Navigating Intergenerational Trauma: Cultivating Healing and Resilience in the Kurdistan Region of Iraq - Hershey, Brenda Hershey (Sulaimani Journal for Humanities, 2026)
This research explores Kurdish intergenerational trauma and resilience, delving into the scientific framework of epigenetics and recognizing trauma signs and patterns within families and communities, specifically within the Kurdish context. 30 Kurdish participants provided insights into their grandparents’ and parents’ trauma experiences, as well as their own, shedding light on present-day life and symptoms connected to intergenerational trauma. Notably, the study uncovers a prevailing trend of prioritizing education as a coping mechanism and pathway to resilience, particularly among younger generations compared to previous generations. The objective of this research is to identify practical ways to support and empower contemporary Generation Z’s and millennials in breaking intergenerational trauma cycles, thereby promoting healed, healthy genetic transmission. As such, it delves into the developing role of social workers in the Kurdistan Region of Iraq (KRI) and avenues through which they can expand their lens to support those affected by intergenerational trauma. Moreover, participants revealed that experiences with local mental health professionals often prove unhelpful or had a negative impact, prompting the dire need for workshops and follow-up programs aimed at enhancing psychological support and training in Kurdistan.
Keywords: Intergenerational trauma; Kurdish communities; Resilience; Posttraumatic stress disorder (PTSD); Collective trauma; Mental health; Social work interventions; KurdistanTable of Contents